Vitamin B12 Deficiency an Unusual Cause of Fever: A Case Report - ., Shyama; Kumar, P.; ., Surabhi (International Journal of Innovative Research in Medical Science, 2019)
Introduction: An unusual case of a 19 year old female, presenting with fever, pallor and hepatosplenomegaly for one month. She had microcytic anemia on peripheral smear examination but her bone marrow aspiration & biopsy revealed a hypercelluar marrow with megaloblastic erythroid hyperplasia. Resolution of fever within 48 hours of Vitamin B12 supplementation, initiated in view of the megaloblastic bone marrow picture & low serumVitamin B12 level, suggests a causal association. Conclusion: Vitamin B12 deficiency seems to be an unusual cause of PUO (Pyrexia of unkown origin) which should be ruled out in every case of PUO.